Transparent and flexible hybrid cover window film: Hard coating/substrate all-in-one composite film for reliable foldable display. (December 2022) - Lee, Yung; Lee, Hyunhwan; Im, Hyeon-Gyun; Jo, Woosung; Choi, Gwang-Mun; Kim, Taek-Soo; Jang, Junho; Bae, Byeong-Soo
Abstract: For realizing foldable displays, transparent and robust cover window film consisting of hard coating and the polymeric substrate should be developed. However, in terms of practical usage, current state-of-the-arts show significant limitations caused by low reliability and incompatibility of hard coating and substrate. Here, we propose a new type of hard coating/substrate all-in-one composite film for the cover window of a foldable display. The film combines siloxane-based hard coating and glass-fabric reinforced hybrid substrate, and that has excellent mechanical robustness and environmental stability. The chemical bond between hard coating layer and hybrid substrate improves compatibility between them, and thereby yields excellent robustness and reliability. The composite film has high optical transparency (90% at 550 nm), surface hardness (6 H), and flexibility (3-mm bending radius). Furthermore, we investigate the reliability of all-in-one film against repeated folding, and against static folding at various severe environments, by direct visualization of strain distribution. Our hard coating/substrate all-in-one film provides a significant breakthrough toward reliable cover window film for future foldable display applications. Graphical abstract: Image 1